Uncovering New Mutations Conferring Azole Resistance in the Aspergillus fumigatus cyp51A Gene - Chen, Peiying; Liu, Musang; Zeng, Qiuqiong; Zhang, Zheng; Liu, Weida; Sang, Hong; Lu, Ling (Frontiers in Microbiology, 2020)
The opportunistic pathogen Aspergillus fumigatus has developed worldwide resistance to azoles largely through mutations in cytochromeP450 enzyme Cyp51. In this study, we indicated that in vitro azole situation results in emergence of azole-resistant mutations. There are previously identified azole-resistant cyp51A mutations (M220K, M220I, M220R, G54E and G54W mutations) and we successfully identified in this study two new mutations (N248K/V436A, Y433N substitution) conferring azole resistance among 18 independent stable azole-resistant isolates. The Galleria mellonella model of A. fumigatus infection experiment verified that Cyp51A mutations N248K/V436A and Y433N reduce efficacy of azole therapy. In addition, a predicted Cyp51A 3D structural model suggested that Y433N mutation causes the reduced affinities between drug target Cyp51A and azole antifungals. This study suggests that drug selection pressure make it possible to isolate unidentified cyp51A mutations conferring azole resistance in A. fumigatus.